PENGARUH KONSENTRASI 6-Benzyl Aminopurine (BAP) PADA MEDIA MS TERHADAP INDUKSI KULTUR JARINGAN CAKRAM BAWANG MERAH (Allium ascalonicum L.) - Fitriya Pebriana; Sri Wiyatiningsih; Pangesti Nugrahani (Plumula : Berkala Ilmiah Agroteknologi, 2018)
Aim of the research is to determine the optimum concentration that has the best effect on the tissue culture induction of onion discus. This research was carried out in August to November 2017, in Biotechnology Laboratory, Agriculture Faculty, UPN "Veteran" Jawa Timur. Completely Randomized Design method was used with 1 factor and repeated for 10 times. Four levels treatment of the growth regulator in this study are Z0 (Control (MS)), Z1 (MS + BAP + 1,5 ppm), Z2 (MS + BAP + 2,5 ppm) and Z3 (MS + BAP + 3,5 ppm). The parameters are the percentage of explant growth potency, growth percentage of the explant roots, growth percentage of the explant shoots, the percentage of stagnancy explant, leaves length and the number of roots and leaves. Data was analyzed used ANOVA (Analysis of Variance) and the Honestly Significant Difference Test 5%. As the results, the addition of the BAP with a concentration of 2,5 ppm is the best treatment for all parameters.